Intrapreneurship concepts for engineers: a systematic review of the literature on its theoretical foundations and agenda for future research - Muhammad Zubair Alam; Nadia Nasir; Chaudhry Abdul Rehman (Journal of Innovation and Entrepreneurship, 2020)
Understanding of intrapreneurship as a phenomenon is somewhat fragmented and inconsistent especially in the case of engineers or engineering firms. This paper seeks to assess the relevant intellectual territory of intrapreneurship or corporate entrepreneurship (CE) by taking a systematic review of relevant research to collect insights into research linking intrapreneurship with engineering firms. The purpose of the systematic review is to identify key concepts in intrapreneurial research with regard to engineers or engineering firms as deliberated by researchers in literature. This systematic literature review (SLR) found that the academic interest of researchers on intrapreneurship has increased over the last decade with a diverse focus. Based on the findings of the review, this study has suggested various areas for future research on the conceptual framework of intrapreneurship, relationship of intrapreneurship with corporate performance, and intrapreneurship for engineers.
Keywords: 650; Intrapreneurship; Corporate entrepreneurship; Engineering firms; Corporate culture; Engineering management; Systematic literature review